17th Chromosome‐Centric Human Proteome Project Symposium in Tehran. Issue 7 (29th March 2018) - Meyfour, Anna; Pahlavan, Sara; Sobhanian, Hamid; Salekdeh, Ghasem Hosseini
Abstract: This report describes the 17th Chromosome‐Centric Human Proteome Project which was held in Tehran, Iran, April 27 and 28, 2017. A brief summary of the symposium's talks including new technical and computational approaches for the identification of novel proteins from non‐coding genomic regions, physicochemical and biological causes of missing proteins, and the close interactions between Chromosome‐ and Biology/Disease‐driven Human Proteome Project are presented. A synopsis of decisions made on the prospective programs to maintain collaborative works, share resources and information, and establishment of a newly organized working group, the task force for missing protein analysis are discussed.